The European Union and the conflict in Ukraine (2014–2018) - Koszel, Bogdan (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2020)
The author has analyzed the European Union’s policy towards Ukraine and put forward a thesis that, in view of Russia’s opposition and the lack of progress in internal reforms, Ukraine has no immediate prospects of EU membership. Although Ukraine has been granted political and financial support in the aftermath of the Russian aggression (annexation of Crimea and war in Donbas), the extent of bilateral cooperation is limited to the signing of an Association Agreement and the abolition of the visa requirement for Ukrainian citizens. Economic sanctions against Russia symbolize the unity of EU member states, but remain the only instrument that can stop the neo-imperial intentions of the Russian Federation. This study employs the methods of systemic, institutional and legal analysis and the decision method.

Autor analizuje politykę UE wobec Ukrainy i stawia tezę, że wskutek oporu Rosji, niechęci wielu państw członkowskich oraz braku efektów w reformach wewnętrznych, Ukraina nie ma perspektywy na członkostwo w UE w najbliższej perspektywie. Chociaż udzielono jej wsparcia politycznego i finansowego, zakres współpracy dwustronnej jest ograniczony do podpisania układu o stowarzyszeniu i zniesienia obowiązku wizowego dla obywateli Ukrainy. Sankcje gospodarcze przeciwko Rosji symbolizują jedność państw członkowskich UE, ale pozostają jedynym instrumentem, który może powstrzymać neoimperialne zamiary Federacji Rosyjskiej. W badaniu wykorzystano metody analizy systemowej, instytucjonalnej i prawnej oraz metodę decyzyjną.
Unia Europejska i konflikt na Ukrainie (2014–2018)
Keywords: European Union; Russia; conflict in Ukraine; Unia Europejska; Rosja; konflikt na Ukrainie